Ночной охотник: [роман] / Роберт Брындза - Брындза Роберт (Новый мировой триллер, 2022)
На корешке: #1. Экземпляры: ЦБ (20230703) / Инвентарный номер: 60099 / Цена: 505.00 / Сис.шифр: 84(4/8) / Авт.знак: Б 89 / ГРНТИ: 17.82 / ББК: 84(4Вел)-44